EFFECT OF CONSUMING TEMULAWAK (CURCUMA XANTHORRHIZA ROXB.) EXTRACT ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Chyntia Desbriyani; Soeharyo Hadisaputro; Titi Suherni; Ari Suwondo; Supriyana Supriyana (Belitung Nursing Journal, 2017)
Background: The dominant factor inhibiting breastfeeding is the lack of milk production. The extract of temulawak (curcuma xanthorrhiza Roxb) is considered having an effect to increase breast milk production. Objective: To examine the effect of temulawak (curcuma xanthorrhiza Roxb) extract to increase milk production in postpartum mothers in the working area of Ambarawa Community Health Center, Indonesia. Methods: This was a quasi-experimental study with non-equivalent control group design conducted on October-December 2016. There were 38 respondents included using consecutive sampling, with 19 assigned in the intervention and control group. Paired t-test and independent test were used for data analysis. Results: Findings showed that there were significant increases of prolactin hormone (p = 0.000), breast milk volume (p = 0.001), baby’s urinary frequency (p = 0.001), baby’s defecation frequency (p = 0.000), and baby’s sleep duration (p = 0.000) after given temulawak (curcuma xanthorrhiza Roxb) extract. Conclusion: Temulawak (curcuma xanthorrhiza Roxb) extract had a significant effect in increasing breast milk production and prolactin levels in postpartum mothers. Thus, it is recommended that temulawak (curcuma xanthorrhiza Roxb) extract can be an option for postpartum mother to increase milk production.